Design Methodology of Base Plates with Column Eccentricity in Two Directions under Bidirectional Moment - Ebadi, Parviz; Soleimani, Mohammad; Beheshti, Mohsen (Salehan Institute of Higher Education, 2018)
Base plate is a critical structural component responsible for transferring loads from the structure to the foundation. By increasing the contact surface between the column foot and the foundation, base plates contribute to more manageable distribution of column forces and the resulting stresses in the substructure. The off-center positioning of column on the base plate, which is sometimes unavoidable because of the limitations imposed by elevator shaft, adjacent buildings, etc. could be a major design issue. This paper investigates the effects of column eccentricity on the design and stress distribution of base plates and the impact of stiffeners on the thickness of these plates. In this investigation, a comparison is made between the superposition method and the finite element method in terms of their evaluation of stress levels under the base plate with column eccentricity. The study also aims to determine the magnitude and distribution of maximum stresses with plateâs thickness and dimensions and columnâs position on the plate taken into account. The results show that the superposition method can be confidently used in the force analysis and design of base plates with column eccentricity under bidirectional moments.